Growth and Development of Bactrocera carambolae Drew & Handcock (Diptera: Tephritidae) on three artificial diets - Toto Himawan; Sri Karindah; Deni Hendrawan (Journal of Tropical Plant Protection, 2012)
AbstractPollard and tofu waste as main component of food for Fruit fly (Bactrocera carambolae) gave better nutrition to support their growth and development than tapioca waste. Pollard, tofu waste and tapioca waste contributed to finish fruit fly life cycles 16, 47, 17, 83 and 18.77 days respectively. Oviposition period of fruit fly on pollard was longer than others. Total number of eggs was laid by fruit fly on pollard about twice to three times higher than others. In addition, longest period of male and female adults was shown by pollard. Net reproduction rate (Ro), mean of life span period (T), intrinsic rate of increase (rm), rate of limit rate of increase (λ) and reproduction value (RVx) shown by life table explained that pollard was suitable material for rearing of B. carambolae as diet.Keywords: artificial diet, B. carambolae, pollard, tofu waste, tapioca waste